Pengaruh nisbah nitrat dan amonium Terhadap aktifitas nitrat reduktase, Kandungan nitrogen, pertumbuhan dan Hasil tanaman pak choi (Brassica chinensis L.)=Effects of Nitrate and Ammonium Ration on Nitrate - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT Growth and yield of plants increased when plants were provided with mixtures of nitrate and ammonium compared with either form alone. Therefore, the objective of this experiment was to determine the optimum of nitrate and ammonium ratio caused an increased in growth and yield of green pak choy (Brassica chinensis L.) The experiment was designed in Randomized Completely Design with five treatments of nitrate ammonium ratios and arranged in four replication. The treatments of nitrate ammonium ratios were: 100/0